Appropriateness of learning environments in preprimary educational institutions: the case of preschools in Bahir Dar city, Ethiopia - Mulugeta Yayeh Worku (International Journal of Child Care and Education Policy)
Abstract This study aimed to examine the appropriateness of learning environments in preprimary institutions, specifically focusing on preschools in Bahir Dar city, Ethiopia. To achieve this, a mixed-methods research approach was employed, guided by an adapted framework for assessing learning environments. Participants included preschool teachers and leaders who were selected through a comprehensive sampling technique. Data were collected using questionnaires and observations, and analyzed both quantitatively (using means, standard deviations, one-sample t-tests, and independent samples t-tests) and qualitatively through a thematic analysis approach. The findings revealed several challenges related to the physical environments, facilities, and classroom conditions within the preschools. The study concludes that, despite some positive efforts, preschools in Bahir Dar city were struggling to provide preprimary education in environments that are unsuitable for children. Finally, the article offers recommendations aimed at improving the learning environments of these institutions.